Intoksikasi Digoksin: Bagaimana Cara Mengenali Dan Penatalaksanaannya - Dewi H Suprobo; Bambang B Siswanto; Yoga Yuniadi; Ganesja M Harimurti (Jurnal Kardiologi Indonesia, 2011)
Background: Digitalis is the oldest compound in cardiovascular medicine that continues to be used in contemporary clinical practice. It is one of the most frequently prescribed medications and has historically been implicated as one of the most common causes of adverse drug reactions. Despite the fact that digitalis preparations have been used  therapeutically for more than 200 years, diagnosis of digoxin toxicity remains difficult. Signs and symptoms associated with toxicity are nonspecific, as are electrocardiographic changes, and the “therapeutic” and “toxic” concentrations overlap.Objective: to present a case report of digoxin intoxication and to review the diagnosis and management of the disease.Summary: We have reported a case related to intoxication of a drug that is one of the most frequently prescribed medications and has historically been implicated as one of the most common causes of adverse drug reactions. This fact is reasonable since digoxin has a narrow margin of safety, where at the therapeutic dosage digoxin could induce intoxication. Moreover the response to this drug is influenced by many factors. Although the general manifestation of digoxin intoxication is not specified, but in patient who are in digoxin therapy with clinical manifestation of digoxin intoxication, we have to put digoxin intoxication as one of our differential diagnosis. The diagnosis is supported by the ECG manifestation and confirmed by the examination of serum digoxin level. Eventhough, normal digoxin level could also induce intoxication. The initial management of digoxin intoxication is early recog -nition that a dysrhythmia and/or noncardiac manifestation may be related to digitalis intoxication and stop the digoxin therapy. Immunotherapy, in hemodynamically stable or unstable patients, is a first-line therapy.